Paleobiological Traits That Determined Scleractinian Coral Survival and Proliferation During the Late Paleocene and Early Eocene Hyperthermals. Issue 2 (22nd February 2019) - Weiss, Anna M.; Martindale, Rowan C.
Abstract: Coral reefs are particularly sensitive to environmental disturbances, such as rapid shifts in temperature or carbonate saturation. Work on modern reefs has suggested that some corals will fare better than others in times of stress and that their life history traits might correlate with species survival. These same traits can be applied to fossil taxa to assess whether life history traits correspond with coral survival through past intervals of stress similar to future climate predictions. This study aims to identify whether ecological selection (based on physiology, behavior, habitat, etc.) plays a role in the long‐term survival of corals during the late Paleocene and early Eocene. The late Paleocene‐early Eocene interval is associated with multiple hyperthermal events that correspond to rises in atmospheric p CO2 and sea surface temperature, ocean acidification, and increases in weathering and turbidity. Coral reefs are rare during the late Paleocene and early Eocene, but despite the lack of reef habitat, corals do not experience an extinction at the generic level and there is little extinction at the species level. In fact, generic and species richness increases throughout the late Paleocene and early Eocene. We show that corals with certain traits (coloniality, carnivorous, or suspension feeding diet, hermaphroditic brooding reproduction, living in clastic settings) are more likely to survive climate change in the early Eocene. These findings have important implications for modern coral ecology and allow us to make more nuanced predictions about which taxa will have higher extinction risk in present‐day climate change. Plain Language Summary: Climate change is negatively impacting corals and reefs today. In order for us to plan for future reef survival, we must learn how corals will respond to these stresses. Past intervals of climate change can provide valuable information about what happens to reefs when the environment changes quickly and how, or if, they recover. We explore the Paleocene and Eocene Stages, which contain a series of high‐temperature events called hyperthermals. We look at the specific traits of the corals at this time, for example, what type of food they ate, how they reproduced, whether they could share resources with one another in a colony, and calculate whether these traits made the corals more likely to survive during this time period. Corals have a relationship with algae that photosynthesize food for the coral, which helps the corals build large skeletons. We show that corals that do not depend on these photosymbionts for food are colonial or live in special habitats and have a better chance of surviving climate change events over long timescales. This research is important for future predictions of coral reef response to climate change; past events, like the one studies, can identify the types of corals that will likely perform best. This information can help scientists figure out how to best protect coral reefs. Key Points: There is no extinction of coral genera in the late Paleocene; however, there are extinctions at the species level Differences in habitat, reproductive strategy, diet, coloniality, and photosymbiotic ability make some corals more susceptible to extinction than others The early Paleogene is an important case study in how coral communities survive extreme environmental perturbations